Determination of the softening curve and fracture toughness of high-strength concrete exposed to high temperature. (November 2015) - Yu, Kequan; Yu, Jiangtao; Lu, Zhoudao; Chen, Qingyang
Highlights: Determine the softening curve of high-strength concrete exposed to high temperature. Determine the fracture parameters of post-fire high strength concrete. Validate the double-K fracture model to the post-fire high-strength concrete. Validate the agreement of analytical and weight function method on calculating fracture parameter. Abstract: Determination of the softening curve and the fracture toughness of high-strength concrete exposed to high temperature from 200 °C to 800 °C employing the three point bending test were presented. The softening curves of post-fire high-strength concrete specimens were calculated by using the inverse analysis. The fracture parameters were obtained by analytical and weight function method. The validation of double-K fracture model to the post-fire high-strength concrete specimens was proved based on the calculated softening curves. The toughness values obtained by the weight function method coincided well with the ones obtained by the analytical method.